Pengaruh Kredibilitas Streamer dan Fitur Interaktif terhadap Niat Beli Konsumen di Live Commerce Marketplace - Adhitya, Wisnu Rayhan; Adhitya, Tiara Reizsa (TIN: Terapan Informatika Nusantara, 2025)
The rapid growth of e-commerce and the popularity of live commerce have created a new competitive landscape for marketplaces in Indonesia, necessitating a deeper understanding of the factors that drive consumer purchase intention. This study aims to analyze the influence of two key elements: Streamer Credibility (the human element) and Interactive Features (the technological element) on Consumer Purchase Intention within the context of live shopping. This study employs a quantitative approach using a survey method, with data collected via an online questionnaire from 100 respondents who are active users of live shopping features on marketplace applications in Indonesia. Data were analyzed using path analysis with Smart-PLS software. The findings reveal that Interactive Features have a strong, significant, and positive influence on Consumer Purchase Intention (path coefficient = 0.730; T-statistic = 10.134). Conversely, and contrary to common assumptions, Streamer Credibility was found to have no significant direct influence on Purchase Intention (path coefficient = 0.006; T-statistic = 0.056). However, the study also found that Interactive Features significantly and positively influence Streamer Credibility perception. The study concludes that the technological aspect (Interactive Features) plays a more dominant role than the human aspect (Streamer Credibility) in directly driving consumer purchase intention within the live commerce ecosystem. This implies that for business practitioners, the main priority should be investing in a seamless and engaging interactive experience as a key strategy to boost sales.